Style and Meaning in Rhoma Irama's Song Lyrics and Their Relevance as Indonesian Language Learning Materials: A Stylistic Study - Nyai Santi; Arjulayana Arjulayana (EDUJAVARE: International Journal of Educational Research, 2026)
Literary works are a medium of expression that utilizes language as the primary means of conveying ideas, feelings, and life values. This study aims to analyze the language styles and meanings found in the song lyrics of Rhoma Irama and to examine their relevance as learning materials for Indonesian language education. The research employed a qualitative approach using content analysis methods. The data consisted of the song lyrics Begadang, Keramat, and Judi, which were analyzed based on the use of figurative language and meaning. Data collection techniques included observation, note-taking, and documentation. The findings reveal that the lyrics contain various language styles such as repetition, metaphor, hyperbole, and imperative expressions used systematically to strengthen the message conveyed. The meanings identified include both denotative and connotative meanings related to moral and social values. Furthermore, the song lyrics have strong potential as contextual learning materials because they help students understand language styles and meanings in real-life contexts while also increasing students’ interest in learning.